PENGELOLAAN PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DALAM PEMBELAJARAN PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA JURUSAN OTOMOTIF - Citra Kasmili (Manajer Pendididikan, 2015)
The purpose of research is to increase the activity and student learning outcomes through the management of STAD cooperative learning. This type of research is the ClassroomAction Research with three cycles. The subjects were students of SMKNN 2 Bengkulu City 2014/2015 school year. The results of this study showed that the activity of students in the firstcycle is not effective while in the second cycle and third cycle has been effective. Student learning outcomes in the first cycle the average value of 74.07 students, then on the second cycle into74.15. Furthermore, in the third cycle students' average score increased to 82.93. Mastery learning classically in the first cycle only reaches 75.60%, then the second cycle increased by 12.20% from the first cycle to be 87.80%. Furthermore, in the third cycle of classical learning completeness increased by 4.88% from the second cycle to be 92.68%Keywords: student learning outcome, activity, cooperative learning, STAD